2018
DOI: 10.1002/anie.201808670
|View full text |Cite
|
Sign up to set email alerts
|

Red‐Shifted Fluorogenic Substrate for Detection of lacZ‐Positive Cells in Living Tissue with Single‐Cell Resolution

Abstract: The Escherichia coli lacZ gene encoding b-galactosidase is awidely used reporter,but few synthetic substrates are available for detecting its activity with single-cell resolution in living samples.O ur recently reported fluorogenic substrate SPiDER-bGal is suitable for this purpose,b ut its hydrolysis product shows green fluorescence emission, and ar ed-shifted analogue is therefore required for use in combination with green fluorescent protein (GFP) markers.Herein, we describe the development of ar ed-shifted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…In the eld of human b-gal recognition, E. coli b-gal, a bacterial enzyme encoded by lacZ, was routinely applied as the substitute enzyme of human b-gal in vitro, 26,27 as well as lacZ-transfected cells enriched by E. coli b-gal were commonly used as model organisms. [26][27][28][29][30][31] However, unlike human b-gal, bacterial b-gal is neither a lysosomal enzyme nor associated with senescence. 20,32,33 Although human b-gal shares a similar catalytic mechanism with E. coli b-gal, by comparing their catalytic domains, we found that this domain of human b-gal was very different from that of E. coli b-gal (pink for human b-gal, yellow for E. coli b-gal, RMSD ¼ 6.236Å), while it was very similar to that of its homologous Aspergillus oryzae (A. oryzae, a fungus) bgal (pink for human b-gal, cyan for A. oryzae b-gal, RMSD ¼ 1.002Å) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In the eld of human b-gal recognition, E. coli b-gal, a bacterial enzyme encoded by lacZ, was routinely applied as the substitute enzyme of human b-gal in vitro, 26,27 as well as lacZ-transfected cells enriched by E. coli b-gal were commonly used as model organisms. [26][27][28][29][30][31] However, unlike human b-gal, bacterial b-gal is neither a lysosomal enzyme nor associated with senescence. 20,32,33 Although human b-gal shares a similar catalytic mechanism with E. coli b-gal, by comparing their catalytic domains, we found that this domain of human b-gal was very different from that of E. coli b-gal (pink for human b-gal, yellow for E. coli b-gal, RMSD ¼ 6.236Å), while it was very similar to that of its homologous Aspergillus oryzae (A. oryzae, a fungus) bgal (pink for human b-gal, cyan for A. oryzae b-gal, RMSD ¼ 1.002Å) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Among the present analytical methods for F À , uorescent probes have caught great attention due to their high sensitivity and selectivity as well as easy operation. [11][12][13][14][15] To date, uorescent probes based on various sensing mechanisms have been reported for the detection of F À , including the uoride-hydrogen bonding interaction, 16,17 boron-uoride complexion 18,19 and uoride induced chemical reaction. [20][21][22][23][24][25][26][27][28][29][30][31][32] Among them the rst two types of probes could only work in non-aqueous media or media with high percentage of organic solvent because the detection signal would be largely hindered in aqueous environment.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, probes with a more red-shifted fluorescence are desired. We developed the red-emitting SPiDER-Red-βGal, which contains a 2 COOH-4CH 2 F-Sirhodol as the core fluorophore and a 2 -carboxy group as an intramolecular nucleophile to adapt the spirocyclic non-fluorescent form at physiological pH (Figure 2a) [102].…”
Section: Enzyme Activationmentioning
confidence: 99%
“…Hence, probes with a more red-shifted fluorescence are desired. We developed the red-emitting SPiDER-Red-βGal, which contains a 2′COOH-4CH2F-Sirhodol as the core fluorophore and a 2′-carboxy group as an intramolecular nucleophile to adapt the spirocyclic non-fluorescent form at physiological pH (Figure 2a) [102]. Upon cleavage of the βGal-moiety the reactive quinone methide can react with nucleophilic functional groups within the cell (e.g., cysteines or lysins of proteins) and hence be immobilized.…”
Section: Enzyme Activationmentioning
confidence: 99%